2013
DOI: 10.1002/bem.21824
|View full text |Cite
|
Sign up to set email alerts
|

Electric field‐induced effects on yeast cell wall permeabilization

Abstract: The permeability of the yeast cells (Saccharomyces cerevisiae) to lipophilic tetraphenylphosphonium cations (TPP(+) ) after their treatment with single square-shaped strong electric field pulses was analyzed. Pulsed electric fields (PEF) with durations from 5 to 150 µs and strengths from 0 to 10 kV/cm were applied to a standard electroporation cuvette filled with the appropriate buffer. The TPP(+) absorption process was analyzed using an ion selective microelectrode (ISE) and the plasma membrane permeability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…This result is very important for performing electroporation and retaining a high viability of the treated cells. Our previous study showed that the detectable electroporation in yeast cells starts after exposure to 5-µs pulses with an electric field strength of approximately 5 kV/cm [37]. Such an electric field corresponds to a 500-V amplitude (dashed line in Figure 7) and such an electric field strength or higher remained for 8.4 µs and 5.5 µs when generated by systems without and with the crowbar circuit, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…This result is very important for performing electroporation and retaining a high viability of the treated cells. Our previous study showed that the detectable electroporation in yeast cells starts after exposure to 5-µs pulses with an electric field strength of approximately 5 kV/cm [37]. Such an electric field corresponds to a 500-V amplitude (dashed line in Figure 7) and such an electric field strength or higher remained for 8.4 µs and 5.5 µs when generated by systems without and with the crowbar circuit, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…It is easy to release only periplasmic space material (recombinant protein) through the pores, while the co-release of contaminants and micronization of the cell debris can be minimized, which offer advantages for the subsequent purification. Besides, Stirke et al (2014Stirke et al ( , 2014a investigated the yeast cell walls disruption using nanosecond high power electrical pulses. Ganeva, Stefanova and Angelova (2015) achieved the selective and efficient recovery of large intracellular proteins from yeast based on the combination of electropermeabilisation and subsequent treatment with lytic enzyme.…”
Section: Non-mechanical Methodsmentioning
confidence: 99%
“…Typically, substances such as fluorescent dyes are loaded into the cells [11,12]. The cells are put into a cuvette with electrodes and after pulsing procedures the release or loading of the dye is observed [13,14].…”
Section: Introductionmentioning
confidence: 99%